2018
DOI: 10.2967/jnumed.118.211094
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Noise and Resolution for Quantitative 177Lu SPECT/CT with xSPECT Quant

Abstract: Quantitative SPECT/CT imaging forms the basis for internal dosimetry in molecular radiotherapies. While the conversion from counts to activity is typically performed based on conversion factors individually measured by each site, a recently introduced commercially available reconstruction (xSPECT Quant) offers a standardized and traceable calibration of SPECT/CT systems. The aim of this work was to assess the characteristics of xSPECT Quant in combination with Lu as one of the most important radionuclides used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…An overview of the most recently applied methods for SPECT/ CT quantification with therapeutically used radionuclides, different phantom geometries, volumes, camera vendors, reconstruction methods, and the related accuracies has been provided by Tran-Gia et al (24). Table 1 shows only publications with reported accuracies of less than 10% (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Image Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the most recently applied methods for SPECT/ CT quantification with therapeutically used radionuclides, different phantom geometries, volumes, camera vendors, reconstruction methods, and the related accuracies has been provided by Tran-Gia et al (24). Table 1 shows only publications with reported accuracies of less than 10% (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Image Quantificationmentioning
confidence: 99%
“…de/molecular-imaging/xspect/xspect-technology/features#). Using this calibration method, Tran-Gia et al (26) showed that a quantification accuracy of less than 2% could be achieved.…”
Section: Image Quantificationmentioning
confidence: 99%
“…However, the xQ applies a CT-derived reconstruction mask to reduce background noise [26]. When comparing the two reconstruction methods, researchers found an unexpected behavior in xQ, where the subset >2 decreased image quality [27,28]. For both…”
Section: Introductionmentioning
confidence: 99%
“…Noise was also added to the activity data assumed to be provided by the SPECT/CT measurement. For SPECT/CT measurements, activity accuracies below 5% are reported in literature for physiological activity concentrations and phantom sizes similar to kidney size . Thus, a noise with FSD SPECT = 5% was used for the simulations.…”
Section: Methodsmentioning
confidence: 99%
“…For SPECT/CT measurements, activity accuracies below 5% are reported in literature for physiological activity concentrations and phantom sizes similar to kidney size. [20][21][22][23] Thus, a noise with FSD SPECT = 5% was used for the simulations. The noise was assumed to be independent of the systematic error of the planar images.…”
Section: C Simulation Of Renal Tiacsmentioning
confidence: 99%